Lupus Eritematosus Sistemik (SLE) dengan Krisis Hipertensi pada Kehamilan: Laporan Kasus - Novierta Prima Kusumandaru; Calcarina Fitriani (PT Kalbe Farma Tbk., 2025)
Introduction: Although SLE prevalence lacks specific Indonesian data, it predominantly affects women of childbearing age. Case: A 24-yearold pregnant woman with a history of SLE experienced worsening shortness of breath, leg swelling, and fatigue since her second month of pregnancy. Hospital admission revealed severe hypertensive crisis, active SLE affecting kidneys, joints, skin, congestive heart failure, and anemia. She underwent rigorous medical treatments and ICU monitoring. Discussion: SLE affects multiple organs. Careful management and monitoring are required during pregnancy for maternal and fetal well-being. Conclusion: Pregnant women with SLE may encounter various pregnancy-related complications. Effective and comprehensive management is vital to achieve favorable outcomes.